System of Exercises on the Improvement of Elimination Skills and the Compression of Scientific Texts. - Фадеева, О. Ю.; Кушнир, И. Н. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article deals with recommendations about working out a preparatory exercises system for mastering the skills of re-coding information in the abstract creation of a secondary scientific text, its reduction up to the set volume without semantic losses of the main sense of a primary source